Tengku Mahkota Pahang breaks fast with UMPSA residents - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 4 April 2024 - His Majesty Tengku Mahkota Pahang Tengku Hassanal Ibrahim Alam Ibni Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah was pleased to meet and break the fast with more than 2,000 students and staff of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).